2015
DOI: 10.1158/0008-5472.can-15-0556
|View full text |Cite|
|
Sign up to set email alerts
|

Multiplex H. pylori Serology and Risk of Gastric Cardia and Noncardia Adenocarcinomas

Abstract: The reported associations with gastric adenocarcinoma and seropositivity to different H. pylori antigens using multiplex serology have not been consistent across studies. We aimed to investigate the association between fifteen different multiplex serology antigens and the risk of gastric cardia (GCA) and gastric non-cardia (GNCA) adenocarcinomas in northeastern Iran, a population with high rates of gastric adenocarcinoma. We included 272 cases of gastric adenocarcinoma (142 GCA, 103 GNCA, and 27 unspecified) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 48 publications
4
33
0
1
Order By: Relevance
“…A meta‐analysis of mostly Western studies showed that the association with H. pylori was found with gastric noncardia cancers (odds ratio, 3.0; 95% confidence interval, 2.3‐3.8) but not with GCA (odds ratio, 1.0; 95% confidence interval, 0.7‐1.4) . However, H. pylori seropositivity is associated with increased risks for GCA in China and Iran but not in other countries such as the United States, Finland, Sweden, and Norway; this suggests that H. pylori may have a distinct association with GCA in China and Iran, perhaps through interactions with other microbiota. Because of these geographic differences, the International Agency for Research on Cancer now includes Asian cardia cancer in their estimates of the H. pylori disease burden .…”
Section: Discussionmentioning
confidence: 92%
“…A meta‐analysis of mostly Western studies showed that the association with H. pylori was found with gastric noncardia cancers (odds ratio, 3.0; 95% confidence interval, 2.3‐3.8) but not with GCA (odds ratio, 1.0; 95% confidence interval, 0.7‐1.4) . However, H. pylori seropositivity is associated with increased risks for GCA in China and Iran but not in other countries such as the United States, Finland, Sweden, and Norway; this suggests that H. pylori may have a distinct association with GCA in China and Iran, perhaps through interactions with other microbiota. Because of these geographic differences, the International Agency for Research on Cancer now includes Asian cardia cancer in their estimates of the H. pylori disease burden .…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, a previous Korean study indicated that the association between PRKAA1 rs13361707 and gastric cancer risk did not vary depending on the tumor site [18]. Shakeri et al observed that HP CagA infection was associated with a significantly increased risk not only for cardia, but for noncardia gastric adenocarcinoma [49]. In contrast, several studies reported that the association between PRKAA1 rs13361707 and gastric cancer risk is stronger in noncardia gastric cancer than in cardia cancer [14,17].…”
Section: Nod2)mentioning
confidence: 89%
“…Shakeri et al. observed that HP CagA infection was associated with a significantly increased risk not only for cardia, but for noncardia gastric adenocarcinoma . In contrast, several studies reported that the association between PRKAA1 rs13361707 and gastric cancer risk is stronger in noncardia gastric cancer than in cardia cancer .…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, they used 272 GC cases from the Golestan cohort and 524 matched controls. CagA and VacA were associated with an increased risk of noncardia GC while surprisingly the inverse occurred for GroEL and NapA . In Latin America, 1776 residents from Mexico, Colombia, and Chile were divided according to the low‐ and high‐risk areas for GC which both had high H. pylori prevalence.…”
Section: Noninvasive Testsmentioning
confidence: 99%